Intergroup exposure in wilderness programming and effects on prospective college belonging among low-income adolescents - Valentino, Salem Wolk, author; Coatsworth, Doug, advisor; Haddock, Shelley, committee member; Riggs, Nathaniel, committee member; Henry, Kimberly, committee member (Colorado State University. Libraries, 2016)
Despite improved rates of college matriculation for low-income students, national disparities in BA attainment remain pervasive in this country. While structural inequities inarguably contribute to lower academic preparedness for this population of students, incoming college freshman with identical academic qualifications will exhibit divergent outcomes based solely on students’ socioeconomic background. Students’ “non-cognitive factors,” or attitudes and beliefs towards learning and school, represent an area of opportunity for youth-serving organizations to intervene with students and influence their college readiness. While the majority of these programs occur within a school setting, outdoor experiential education (OEE) is another venue available to low-income youth to bolster these skills. Moreover, exposure to upper-income, white youth in the context of these facilitative settings can begin to prepare them socially for the challenges of being underrepresented in a college setting. The current study used contact theory to frame whether intergroup exposure while on an OEE wilderness expedition would contribute to students’ beliefs regarding prospective college belonging through improved empathy and perspective-taking. The sample consisted of 246 high-school students participating in the Summer Search program who went on summer wilderness expeditions either with their peers in the program or with upper-income, majority-white youth. Results revealed that intergroup exposure did not uniquely predict improved college belonging; however, particular peer- and adult-related group processes on the trip, social exclusion, negative peer dynamics, positive adult behaviors, and negative adult behaviors, all exhibited effects on college belonging indirectly through empathic perspective-taking. Social exclusion and positive adult behaviors also exhibited direct effects on college belonging. The effects of group processes did not differ based on intergroup exposure. Implications for practice and directions for future research are discussed.